Analyzing Satisfaction Level and Promotion Effectiveness of Honda Middle Class Motorsport (Case Study of PT Daya Adicipta Mustika) - Rasyad, Irfan Fauzan; Wandebori, Harimukti (Journal of Business and Management, 2013)
Currently PT. Daya Adicipta Mustika is trying to dominate the market of motorcycle sport category especially the middle-class in Bandung. To stay competitive and increase sales and improve product quality and company performance, companies need to know the level of customer satisfaction and the effectiveness of the promotion of the company.Objectives of this research are: (1) Identify the characteristics of PT. Daya Adicipta Mustika customers, (2) Analyze PT. Daya Adicipta Mustika customer satisfaction, (3) Analyze the effectiveness of promotions done by PT. Daya Adicipta Mustika, (4) Analyze the relationship between customer satisfactions with the effectiveness of promotions on PT. Daya Adicipta Mustika. Data used in this study is primary data and secondary data. Primary data obtained through interviews with company management and questionnaires deployment to PT. Daya Adicipta Mustika customers. Secondary data were obtained from literatures, internets and previous studies. The selection of respondents was conducted using convenience sampling with the number of respondents of 100 respondents. Methods of analysis used in data processing are Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI), EPIC Model and Pearson Correlation Analysis. Based on IPA and CSI calculation, it can be seen that level of customer satisfaction index of Honda middle-class motorsport was 74.50%, that value still under it competitor Yamaha that given 92.7% based on Roy Morgan research in Customer Satisfaction Award of the Year in Indonesia in 2012 so Honda customer satisfaction value still not enough to become market leader in Honda middle class motorsport. Based on EPIC model, it can be seen that value of EPIC Rate is 2.41, Honda still need to increase their promotion communication with customers to compete with Yamaha in this segment. Based on Pearson correlation analysis, it can be seen that coefficient correlation of the customer satisfaction level and promotion effectiveness is positive 0.476 (47.6%) were in the range between 0.41 â€“ 0.70.Keywords:Â  marketing mix, service quality, customer perception, promotion, Honda----------------------------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.